(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This work analyzes the impact, opportunities, and practical mechanisms of crowdfunding platforms on innovative development. Compared to traditional financing instruments, crowdfunding is characterized by openness, a large number of participants, and the ability to quickly test ideas. The study examines the experience of global platforms such as Kickstarter and Indiegogo, as well as the possibilities of implementing this system in Uzbekistan. It is also substantiated that crowdfunding is a convenient financial alternative for startups, young innovators, and social projects. Recommendations on the topic emphasize the need to form a national crowdfunding infrastructure in Uzbekistan, create a legal framework, and improve financial literacy.